Teachers’ Ability in Applying Historical Literacy in History Learning in Senior High School - Kurniawati, Kurniawati; Winarsih, Murni; Rahman, Ayuningtias (Paramita: Historical Studies Journal, 2022)
The purpose of this study was to determine the ability of teachers to apply historical literacy to history learning in high school and the obstacles faced by teachers in the application of historical literacy. This research is a qualitative research with problem analysis using a case study type of multi-case analysis carried out during Distance Learning (PJJ) during the COVID-19 pandemic at Labschool Jakarta High School and Public High School 30 Jakarta in 2020. Data collection was conducted using in-depth interviews, document studies, and field notes. Analysis and interpretation of the data show that (1) history learning during the distance learning period at SMA Labschool Jakarta and SMA Negeri 30 Jakarta is still running conducive, but this condition also affects teacher and student interactions to be more limited in learning; (2) The teacher has been able to apply historical literacy in history learning in accordance with a summary of the main aspects of the concept of historical literacy; (3) The obstacles faced by teachers in applying historical literacy are mainly to teachers' conceptual understanding of historical literacy which is still at the stage of traditional understanding of reading and writing, low levels of student literacy, and becomes increasingly complex when implementing PJJ, teachers have difficulty bringing innovations in application of historical literacy due to limited interaction space and duration of teaching time and presenting historical literacy as an effort to foster critical thinking skills.Tujuan penelitian ini adalah untuk mengetahui kemampuan guru dalam menerapkan literasi sejarah pada pembelajaran sejarah di SMA dan kendala yang dihadapi guru dalam penerapan literasi sejarah. Penelitian ini merupakan penelitian kualitatif dengan analisis masalah menggunakan jenis studi kasus analisis multi kasus yang dilakukan pada Pembelajaran Jarak Jauh (PJJ) pada masa pandemi COVID-19 di SMA Labschool Jakarta dan SMA Negeri 30 Jakarta tahun 2020. Pengumpulan data dilakukan dilakukan dengan wawancara mendalam, studi dokumen, dan catatan lapangan. Analisis dan interpretasi data menunjukkan bahwa (1) pembelajaran sejarah pada masa pembelajaran jarak jauh di SMA Labschool Jakarta dan SMA Negeri 30 Jakarta masih berjalan kondusif, namun kondisi ini juga mempengaruhi interaksi guru dan siswa menjadi lebih terbatas dalam pembelajaran; (2) Guru telah mampu menerapkan literasi sejarah dalam pembelajaran sejarah sesuai dengan rangkuman aspek-aspek pokok konsep literasi sejarah; (3) Kendala yang dihadapi guru dalam menerapkan literasi sejarah terutama pada pemahaman konseptual guru tentang literasi sejarah yang masih pada tahap pemahaman tradisional membaca dan menulis, rendahnya tingkat literasi siswa, dan menjadi semakin kompleks pada saat pelaksanaan PJJ, guru kesulitan menghadirkan inovasi dalam penerapan literasi sejarah karena terbatasnya ruang interaksi dan durasi waktu pengajaran serta menghadirkan literasi sejarah sebagai upaya menumbuhkan kemampuan berpikir kritis.Cite this article: Kurniawati, WInarsih, M., Rahman, A. (2022). Teachers’ Ability in Applying Historical  Literacy in History Learning in Senior High School. Paramita: Historical Studies Journal, 32(1), 127-137. http://dx.doi.org/10.15294/paramita.v32i1.28405